2013
DOI: 10.1186/1472-6955-12-19
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pain at pressure areas and pressure ulcers in hospitalised patients

Abstract: BackgroundPatients with pressure ulcers (PUs) report that pain is their most distressing symptom, but there are few PU pain prevalence studies. We sought to estimate the prevalence of unattributed pressure area related pain (UPAR pain) which was defined as pain, soreness or discomfort reported by patients, on an “at risk” or PU skin site, reported at a patient level.MethodsWe undertook pain prevalence surveys in 2 large UK teaching hospital NHS Trusts (6 hospitals) and a district general hospital NHS Trust (3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
72
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 19 publications
6
72
0
3
Order By: Relevance
“…8 To determine if patients had localised skin pain on any pressure area skin site, they were asked two screening questions with yes or no responses: (1) at any time, do you get pain, soreness or discomfort at a pressure area (prompt: back, bottom, heels, elbows or other as appropriate to the patient)? and (2) do you think this is related to either; your PU OR lying in bed for a long time OR sitting for a long time?7 8…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 To determine if patients had localised skin pain on any pressure area skin site, they were asked two screening questions with yes or no responses: (1) at any time, do you get pain, soreness or discomfort at a pressure area (prompt: back, bottom, heels, elbows or other as appropriate to the patient)? and (2) do you think this is related to either; your PU OR lying in bed for a long time OR sitting for a long time?7 8…”
Section: Methodsmentioning
confidence: 99%
“…8 We conducted two large multicentre prevalence surveys in the hospital8 and community7 setting. It was identified that 12.6% (233/1769) of hospital patients with no observable PUs reported pressure area related pain.…”
Section: Introductionmentioning
confidence: 99%
“…Pressure ulcers (PUs) are a serious problem in health care settings globally. A PU is “a localized injury to the skin and/or the underlying tissue, usually over a bony prominence, as a result of pressure or pressure in combination with shear.” PUs cause considerable patient suffering from pain, affect the patient's quality of life emotionally, physically, and socially, and even put patients at increased risk of death . In addition, PUs lead to an economic burden on health care systems …”
Section: Introductionmentioning
confidence: 99%
“…However, international studies have an incidence ranging from 4.5% to 25.2% (United Kingdom), and a prevalence of 2.9% to 8.34% (Spain), 14.8% (England) and 19.1% (USA) in home care. [2][3][4][5] As regards to Brazil, there are few studies on the prevalence and incidence of the disease, however, with regard to home care, there are studies which showed a 41.2% to 59% risk for the development of pressure injury and a prevalence of between 8% and 23%, this is a cause for concern as it is something which can be prevented in up to 95% of cases, as determined by the Rio de Janeiro Declaration on the Prevention of Pressure Injury. [6][7][8][9][10] It is known that care for people with pressure injuries should occur in high and medium complexity health services, as well as Primary Health Care (phc), under the care of the Family Health Team (ESF), which refers to the establishment of guidelines which guide the practice of prevention, with the need to move towards health promotion actions.…”
Section: Introductionmentioning
confidence: 99%